Cretaceous raliolarians from DSDP Leg 89 holes - André Schaaf (PANGAEA, 1986)
Radiolarian faunas from Leg 89 are scarce and poorly preserved. Upper Cretaceous assemblages are reworked. The oldest and lowest assemblage recognized was of the Archaeospongoprunum cortinaensis Zone in Hole 585. The biochronology of two levels in Hole 462A are revised as follows: the lowest assemblage of species useful for biochronology is of the Cecrops septemporatus Zone (early Hauterivian); the age of a higher sample is late Tithonian-early Berriasian, indicating reworking of older sediment into the Nauru Basin.
Supplement to: Schaaf, A (1986): Radiolaria from Deep Sea Drilling Project Leg 89. In: Moberly, R; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 89, 321-326, https://doi.org/10.2973/dsdp.proc.89.108.1986